Upaya Meningkatkan Hasil Belajar Menulis Kalimat Past Tense Melalui Model Pembelajaran Discovery Learning Pada Siswa Kelas VIII F SMP Negeri 1 Ngluwar Tahun Pelajaran 2021/2022 - Nurohmah, Indriyani (Faculty Of Education, 2022)
One of the English materials with a low level achievement is writing sentences in Past tense. To overcome this problem, aclass action research (PTK) was conducted using Discovery learning model. with tittle Upaya Meningkatkan Hasil Belajar Menulis Kalimat Past tense Melalui Model Pembelajaran Discovery learning Pada Siswa Kelas VIIIF SMP Negeri 1 Ngluwar Tahun Pelajaran 2021/2022.”The purpose of this study was to find out the increase in learning outcomes in the skillsof writing sentences in Past tense in class VIIIF students of SMP Negeri 1 Ngluwar in the 2021/2022 academic year. The research subjects were students totaling 32 people, the data of the reseach was obtained from qualitative data in the form of observation data on the activites of the teacher and the students and from quantitative data in the form of studentlearning outcomes test. In the first cycle, it was found that among 32 students, 21studentsgot a completey scope of Minimum Clompeteness Criteria (KKM ), the percentage of classical completeness is 65,63%.Whilein thesecondcycleit was found that 28 students got a completely scope of Minimum Clompeteness Criteria (KKM ), the percentage of classical completeness is 87,5 %, with the increasing 21,87 poin. Based on the results of the study, teaching and learning using the Discovery Learning model can improve the learning outcomes in the skills of writing sentences in Past tense in Class of SMP Negeri 1 Ngluwar in the 2021/2022 academic year.